Wind Variability and its Impact on IOD and MJO Phenomena in Western Waters: Variabilitas Angin dan Dampaknya terhadap Fenomena IOD dan MJO di Perairan Barat - Ahmad Syamsudin Tohari; Lizalidiawati Lizalidiawati; Irkhos Irkhos (Academia Open, 2023)
This study investigates the interplay between wind variability and the Indian Ocean Dipole (IOD) and Madden-Julian Oscillation (MJO) phenomena in the western waters of Sumatra during the period 1982-2021. Utilizing monthly average wind data from satellite images, the research employs a comprehensive approach involving GrADS, Microsoft Excel, Surfer, Matlab, and Panoply software for data processing. The analysis reveals distinct wind patterns and varying IOD and MJO phases, with notable instances such as a positive IOD in October 1982 and a negative IOD in March 1983, coupled with strong MJO activity in February 1982 and weak activity in October 1983. This research underscores the significant influence of wind conditions on the dynamics of IOD and MJO phenomena in the studied region, contributing to a deeper understanding of ocean-atmosphere interactions. Highlight: Temporal Analysis: This study examines wind variability's interplay with IOD and MJO phenomena over three decades, revealing distinct patterns and phases in the western waters of Sumatra. Comprehensive Approach: Utilizing advanced software tools, the research processes satellite-derived wind data, shedding light on the complex dynamics of ocean-atmosphere interactions. Phenomena Dynamics: Notable occurrences, including positive and negative IOD events and varying MJO strengths, emphasize the profound impact of wind conditions on shaping the behavior of these critical climate phenomena, contributing to enhanced understanding and prediction. Keyword: Wind Variability, Indian Ocean Dipole (IOD), Madden-Julian Oscillation (MJO), Ocean-Atmosphere Interactions, Western Sumatra